Influence of some Bio chars and organic fertilizers on some biological parameters of sweet corn (Zea mays L.) at Sulaimani Governorate, IKR. - Bakhtyar abdulkadir Rashid; Akram Othman Esmail (Zanco Journal of Pure and Applied Sciences, 2022)
This study was conducted in July 2021 until October 2022 at kanipanka research farm, Sulaimani governorate, IKR with GPS readings of 350 22’ 25.3” N, 450 43’ 24.5” E to test, the influence of five levels (0, 14, 28, 42 and 56 ton ha-1) of some treatments such as control (a1), rise husk bio char (a2), oak charcoal (a3) and poultry manure (a5) which equivalent to 0, 0.4, 0.8, 1.2 and 1.6% w/w% of soil, also five levels (0, 12.5, 25, 37.5 and 50 kg ha-1) of Humic acid (a4) to examine the quantity and quality of sweet corn. Additionally 240kg ha-1 of triple super phosphate was added to each experimental unit. The result showed that the poultry manure has a great effect on sweet corn compared to biochars due to high content of phosphorus and nitrogen in poultry manure, also biochars such as rice husk and charcoal were effect on TSS%, P concentration in seed and plants. The highest yield (20.61ton ha-1) was recorded from the interaction treatments of (42 ton ha-1) of poultry manure, also the highest protein %, oil % and chlorophyll content (14.90%, 5.93% and 44.80 SPAD value) were recorded from the interaction treatments of 56 ton ha-1 of poultry manure.